ADAPTATION OF LANGUAGE LEARNING STRATEGIES AMONG HYPERPOLYGLOTS: THE ROLE OF SOCIOCULTURAL CONTEXTS AND RESOURCES - Osle, Angel (LLT Journal: A Journal on Language and Language Teaching, 2025)
This study investigates how hyperpolyglots—individuals proficient in six or more languages—adapt their language learning strategies in response to sociocultural contexts and resource availability. Using a qualitative-dominant mixed-methods design, the research draws on in-depth interviews and an adapted Strategy Inventory for Language Learning (SILL) questionnaire completed by 30 hyperpolyglots from diverse linguistic and cultural backgrounds. Thematic analysis revealed five key findings: strategic flexibility across sociocultural contexts, the central role of social interaction as a motivational and practical scaffold, creative innovation in resource-scarce environments, language-specific strategy differentiation, and integrative, metacognitive planning. These findings extend previous models of strategy use by foregrounding the role of culture, community, and learner-generated tools in multilingual success. This study contributes to sociocultural theory in applied linguistics by highlighting how real-world conditions and interactions shape strategy selection and effectiveness.